2018
DOI: 10.1111/anu.12798
|View full text |Cite
|
Sign up to set email alerts
|

UntargetedGCMSmetabolomics reveals metabolic differences in the Chinese mitten‐hand crab (Eriocheir sinensis) fed with dietary palm oil or olive oil

Abstract: Palm oil (PO) and olive oil (OO) have been widely used in animal diets, but the knowledge of metabolic change in animals fed a diet with different oil sources is limited. Here, we compared the metabolic differences in the Chinese mitten crab fed with PO and OO as the main dietary lipid sources by performing GC‐MS‐based serum metabolomics assays and traditional nutritional assessments. The crab fed OO displayed lower lipid accumulation and oxidative stress in the hepatopancreas than those in the crab fed PO. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…GC derivatization was performed for metabolic profiling on the GC-MS [29]. The lyophilized samples were re-dissolved in 100 µL of 20 mg/mL methoxyamine hydrochloride in pyridine and incubated at 37 • C for 1 h for carbonyls protection [30].…”
Section: Gc-ms Analysis Of Extracellular Metabolitesmentioning
confidence: 99%
“…GC derivatization was performed for metabolic profiling on the GC-MS [29]. The lyophilized samples were re-dissolved in 100 µL of 20 mg/mL methoxyamine hydrochloride in pyridine and incubated at 37 • C for 1 h for carbonyls protection [30].…”
Section: Gc-ms Analysis Of Extracellular Metabolitesmentioning
confidence: 99%
“…One work reported that crab fed the olive oil diet grew faster and had lower concentrations of hepatic glycogen, TAG, and oxidative stress biomarkers, while metabolites related to glycolysis and the tricarboxylic acid cycle, intermediate for valine and leucine synthesis, and intermediate for glutathione synthesis were up-regulated compared with the perilla oil [43]. The other work described differences when comparing olive oil vs. palm oil intake in five metabolic pathways, including alanine, aspartate and glutamate metabolism, lysine biosynthesis and degradation metabolism, arginine and proline metabolism, pyrimidine metabolism and propanoate metabolism [44]. These data are different from those obtained by Guasch-Ferré et al (2020) in humans with T2DM [32], but we think that differences in human and crab metabolisms make it difficult to compare results.…”
Section: Metabolomics Approaches In Experimental Studiesmentioning
confidence: 97%
“…Gas chromatography-mass spectrometry (GC-MS) is generally used to resolve volatile (or can be volatilized) compounds such as monosaccharides, amino acids, organic acids and nucleosides in metabolomics analysis (Ma et al, 2018). More importantly, GC-MSbased metabolomics analysis provides an understanding of the metabolic profile of different dietary components, such as dietary oils in fish and crustaceans (Ma et al, 2017(Ma et al, , 2018Qiu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography-mass spectrometry (GC-MS) is generally used to resolve volatile (or can be volatilized) compounds such as monosaccharides, amino acids, organic acids and nucleosides in metabolomics analysis (Ma et al, 2018). More importantly, GC-MSbased metabolomics analysis provides an understanding of the metabolic profile of different dietary components, such as dietary oils in fish and crustaceans (Ma et al, 2017(Ma et al, , 2018Qiu et al, 2017). Besides, GC-MS analysis has been used to identify potential biomarkers for the assessment of the meat quality of white-fleshed fish (Mabuchi, Ishimaru, Tanaka, Kawaguchi, & Tanimoto, 2018), as well as the larva quality of hatchery-reared mussels (Young et al, 2015).…”
Section: Introductionmentioning
confidence: 99%